Magnesium-based composite material, pre-magnesium silicon oxide material, preparation method and application of pre-magnesium silicon oxide material and lithium ion battery

By reacting magnesium-based composite materials with silicon oxide to form premagnesium silicon oxide materials, the problem of low first-time Coulomb efficiency and high expansion rate in lithium-ion batteries is solved, and higher specific capacity and more stable cycling performance are achieved.

CN119674033AActive Publication Date: 2025-03-21SHANGHAI SHANSHAN NEW MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411929081.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-21
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

Silicon-based anode materials have problems with low first-time Coulomb efficiency and high expansion rates in lithium-ion batteries, resulting in low actual available battery power and cycle stability of the battery.

Method used

Magnesium-based composite materials are used as magnesium source to form premagnesium silicon oxide material by reacting with silicon oxide, improving the uniformity of premagnesium reaction of silicon oxide, and improving the specific capacity and structural stability of the material.

Benefits of technology

It significantly improves the first Coulomb efficiency and specific capacity, improves the volume stability and cycling performance of the material, reduces the expansion rate of the battery, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674033A_ABST
    Figure CN119674033A_ABST
Patent Text Reader

Abstract

The invention relates to a magnesium-based composite material, a pre-magnesium silicon oxide material, a preparation method and application of the pre-magnesium silicon oxide material and a lithium ion battery. The magnesium-based composite material is composed of a magnesium matrix, MgO and Mg2Si, wherein the MgO and the Mg2Si are distributed on the outer surface of the magnesium matrix. MgO and Mg2Si are uniformly distributed on the outer surface of the magnesium matrix in a granular form; the mass ratio of the magnesium matrix to MgO is greater than 1.71: 1; and the mass ratio of the magnesium matrix to Mg2Si is greater than 2.45: 1. The magnesium-based composite material disclosed by the invention is used as a magnesium source, so that the uniformity of a silicon monoxide pre-magnesium reaction is greatly improved, and the specific capacity and the structural stability of the material can be effectively improved. The magnesium-based composite material and the pre-magnesium silicon oxide material are simple in preparation method, controllable in reaction and free of special environment, and have good operability and industrialization potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a magnesium-based composite material, a pre-magnesium silicon oxide material, a preparation method and application thereof, and a lithium ion battery. Background Art

[0002] Silicon-based materials have high theoretical gram capacity (1700-4200 mAh / g) and low electrochemical lithium insertion potential (about 0.4V vs. Li / Li + ), and its resource reserves are abundant, so it is widely regarded as the most promising next-generation new negative electrode material. Compared with traditional graphite negative electrode materials, silicon-based materials have significant energy density advantages and are expected to promote battery technology to develop in the direction of higher performance and longer battery life. However, although silicon-based materials have great advantages in theory, they still face a series of technical difficulties in practical applications, mainly manifested in low first coulomb efficiency and high expansion rate.

[0003] Low initial coulombic efficiency means that during the first charge and discharge process of the battery, the actual available power is far lower than the theoretical value due to the irreversible capacity loss of silicon-based materials. The high expansion rate is due to the significant volume expansion of silicon during the lithium ion embedding process, which not only causes damage to the internal structure of the battery, but also seriously affects the cycle stability and life of the battery. Therefore, solving the problems of the initial coulombic efficiency and expansion of silicon-based negative electrode materials has become the key to improving their application performance.

[0004] In order to solve these problems, pre-magnesium technology came into being. Pre-magnesium technology can improve the electrochemical performance of silicon-based materials to a certain extent by introducing magnesium elements on the surface of silicon-based materials. Specifically, pre-magnesium technology can effectively improve the first coulombic efficiency of silicon-based materials and reduce irreversible capacity loss by improving the initial charge-discharge process of the material. In addition, pre-magnesium can also inhibit the expansion of silicon-based materials to a certain extent and reduce the volume change during the charge and discharge process, thereby improving the cycle life and stability of the battery.

[0005] Pre-magnesium technology mainly includes gas phase-gas phase pre-magnesium, gas phase-solid phase pre-magnesium and solid phase-solid phase pre-magnesium. Gas phase-gas phase pre-magnesium is further divided into front-end pre-magnesium and back-end pre-magnesium according to the different silicon oxide materials. Among them, the uniformity of gas phase-gas phase pre-magnesium is higher than that of gas phase-solid phase pre-magnesium and solid phase-solid phase pre-magnesium, so it has good inhibition of silicon-based material expansion, but there is little difference in the improvement of the first coulomb efficiency. Although the uniformity of gas phase-gas phase pre-magnesium is good, its harsh process conditions are not conducive to its large-scale production. In addition, although the pre-magnesium technology improves the first coulomb efficiency, it also causes a decrease in specific capacity.

[0006] From an industrial perspective, how to improve the uniformity of gas-solid phase pre-magnesium and solid-solid phase pre-magnesium, and how to reduce the loss of specific capacity after pre-magnesium are the most important steps in advancing silicon-based materials. Summary of the invention

[0007] The technical problem to be solved by the present invention is to overcome the defects of low first coulombic efficiency and high expansion rate faced by silicon-based negative electrode materials in the prior art. Although the pre-magnesium technology can improve the first coulombic efficiency and inhibit the expansion, it still has the defects of decreased specific capacity and complex large-scale production process. A magnesium-based composite material, a pre-magnesium silicon oxide material and its preparation method, application and lithium-ion battery are provided. The magnesium-based composite material of the present invention, as a magnesium source, greatly improves the uniformity of the pre-magnesium reaction of silicon oxide, and can effectively improve the specific capacity and structural stability of the material. The pre-magnesium silicon oxide material of the present invention has excellent volume stability and cycle performance, and significantly improves the first coulombic efficiency and specific capacity. The preparation method of the magnesium-based composite material and the pre-magnesium silicon oxide material of the present invention is simple, the reaction is controllable, no special environment is required, and it has good operability and industrialization potential.

[0008] The present invention solves the above technical problems through the following technical solutions:

[0009] The present invention provides a magnesium-based composite material, which comprises a magnesium matrix and MgO and Mg2Si distributed on the outer surface of the magnesium matrix;

[0010] The MgO and the Mg2Si are evenly distributed on the outer surface of the magnesium matrix in a granular form;

[0011] The mass ratio of the magnesium matrix to the MgO is greater than 1.71:1;

[0012] The mass ratio of the magnesium matrix to the Mg2Si is greater than 2.45:1.

[0013] Preferably, the mass ratio of the magnesium matrix to the MgO is 29.1:1.

[0014] Preferably, the mass ratio of the magnesium matrix to the Mg2Si is 41.5:1.

[0015] The present invention also provides a method for preparing a magnesium-based composite material, which comprises the following steps: uniformly mixing magnesium powder and SiO2 powder, and heating them for reaction;

[0016] The mass ratio of the magnesium powder to the SiO2 powder is greater than 2.3:1;

[0017] The temperature of the heating reaction is ≤900°C.

[0018] The type of the magnesium matrix is ​​a magnesium matrix conventionally selected in the art, such as pure magnesium.

[0019] Preferably, the method for preparing the magnesium-based composite material satisfies one or more of the following conditions:

[0020] (1) The mass ratio of the magnesium powder to the SiO2 powder is (20-100):1, more preferably (24-99):1, for example 39:1;

[0021] (2) The temperature of the heating reaction is 200°C-900°C, more preferably 400°C-600°C;

[0022] (3) The uniform mixing operation is carried out in a mixer;

[0023] (4) The heating reaction is carried out in a vacuum furnace;

[0024] (5) The heating reaction time is 2h-6h, for example 4h;

[0025] (6) The vacuum degree of the heating reaction is ≤10 -5 Pa.

[0026] In this scheme, the mass ratio of magnesium powder to SiO2 powder is designed to achieve better structural control. This ratio ensures that magnesium powder and SiO2 powder can fully react during the reaction process to form a uniform magnesium-based composite material structure, optimize the microstructure of the material, and improve the mechanical properties, thermal stability and electrochemical properties of the composite material.

[0027] The present invention also provides a magnesium-based composite material, which is prepared by the above-mentioned method for preparing the magnesium-based composite material.

[0028] The present invention also provides a pre-magnesium silicon oxide material, the pre-magnesium silicon oxide material comprises a core and a carbon coating layer coated outside the core, the core comprises the magnesium-based composite material, magnesium silicate compound and silicon oxide as described above; the carbon coating layer is an amorphous carbon layer;

[0029] The magnesium-based composite material and the magnesium silicate compound are deposited in the pores and on the surface of the silicon oxide;

[0030] The magnesium silicate compounds are MgSiO3 and Mg2SiO4;

[0031] The weight percentage of silicon element in the pre-magnesium silicon oxide material is 49 wt%-54 wt%, for example 49.6 wt%;

[0032] and / or, the weight percentage of magnesium element in the pre-magnesium silicon oxide material is 2.5 wt%-12.5 wt%, for example, 7.5 wt%;

[0033] and / or, the weight percentage of oxygen element in the pre-MgO-SiO material is 34 wt%-41.5 wt%, for example, 39.8 wt%;

[0034] and / or, the weight percentage of carbon element in the pre-magnesium silicon oxide material is 2.5 wt%-4 wt%, for example, 3.1 wt%;

[0035] Wherein, wt% is the percentage of the weight of each element to the total weight of the pre-magnesium silicon oxide material.

[0036] The present invention also provides a method for preparing a pre-magnesium silicon oxide material, comprising uniformly mixing the magnesium-based composite material and silicon oxide as described above, and calcining to obtain a mixed material A;

[0037] Then, the mixed material A is pickled in an acidic solution to obtain a mixed material B;

[0038] The mixed material B is then carbon coated in a mixed gas containing a carbon source gas and an inert gas.

[0039] In this scheme, by introducing magnesium-based composite materials, the uniformity of silicon oxide pre-magnesium reaction is effectively improved, avoiding the performance degradation caused by uneven reaction in traditional methods. Compared with the traditional solid-solid phase pre-magnesium method, the use of magnesium-based composite materials significantly improves the uniformity of the reaction process, making the reaction product more stable, thereby improving the overall performance of the material.

[0040] Preferably, the method for preparing the pre-magnesium silicon oxide material satisfies one or more of the following conditions:

[0041] (1) The mass ratio of the silicon oxide to the magnesium-based composite material is greater than 2.3:1, for example, 9:1;

[0042] (2) The uniform mixing operation is carried out in a mixer;

[0043] (3) After the mixing is uniform, the step of replacing with an inert gas is also included before the calcination;

[0044] Further preferably, the inert gas is a combination of one or more of argon, helium or nitrogen, such as argon;

[0045] Further preferably, the inert gas replacement is carried out in a rotary kiln, wherein the rotation speed of the rotary kiln is more preferably 0.5 r / min-2 r / min, for example 1 r / min;

[0046] Further preferably, the flow rate of the inert gas is 0.5 L / min-2 L / min, for example 1 L / min;

[0047] Further preferably, the inert gas replacement time is 1h-4h, for example 2h;

[0048] (4) The calcination reaction temperature is ≤ 900°C, more preferably 600-900°C, for example 750°C;

[0049] (5) The calcination reaction time is 4h-8h, for example 6h;

[0050] (6) The heating rate from room temperature to the calcination reaction temperature is 5°C / min-15°C / min, for example, 10°C / min;

[0051] (7) The acidic solution is a combination of one or more of hydrochloric acid, acetic acid or sulfuric acid;

[0052] More preferably, the concentration of the acidic solution is 3%-8%, for example 3%-6%, where % is the mass percentage concentration;

[0053] More preferably, the volume ratio of the mixed material A to the acidic solution is less than or equal to 2:1, and more preferably (0.5-2):1;

[0054] (8) The pickling process also includes a water washing process;

[0055] (9) The pickling process also includes a drying process;

[0056] More preferably, the drying temperature is ≤200°C, more preferably 120°C-200°C, and the drying time is ≤48h, more preferably 3h-48h;

[0057] (10) The carbon source gas is acetylene;

[0058] (11) The inert gas is a combination of one or more of argon, helium or nitrogen, such as argon;

[0059] (12) The flow rate ratio of the inert gas to the carbon source gas is 1:(1-1.5);

[0060] More preferably, the flow rate of the inert gas is 2 L / min, and the flow rate of the carbon source gas is 2.5 L / min;

[0061] (13) The carbon coating reaction temperature is 600°C-1000°C, for example 800°C;

[0062] (14) The heating rate from room temperature to the reaction temperature of carbon coating is 1°C / min-10°C / min, for example, 5°C / min;

[0063] (15) The reaction time of the carbon coating is 0.5 h -2 h, for example 1 h;

[0064] (16) The ratio of the mixed gas to the mixed material B is 0.010 L / g to 0.200 L / g, where L / g refers to the volume of the mixed gas required per gram of the mixed material B;

[0065] More preferably, the dosage ratio of the mixed gas to the mixed material B is 0.135 L / g.

[0066] The present invention also provides a pre-magnesium silicon oxide material, which is prepared by the above-mentioned preparation method.

[0067] The present invention also provides a use of the above-mentioned pre-magnesium silicon oxide material in the preparation of pole pieces.

[0068] Preferably, the electrode is a negative electrode;

[0069] Preferably, the preparation method of the pole piece is to mix the pre-magnesium silicon oxide material, the binder and the conductive agent, apply the mixture on the copper foil, vacuum dry, roll and cut the mixture.

[0070] The present invention also provides a lithium ion battery, which comprises the pre-magnesium silicon oxide material as described above.

[0071] The positive and progressive effects of the present invention are:

[0072] (1) Solving the problem of uniformity of solid-solid pre-magnesium reaction: Traditional methods usually improve reaction uniformity by coating a carbon layer on the surface of silicon-based materials or adding molten salts to reduce the temperature and form an inert protective layer. The present invention uses magnesium-based composite materials to achieve one-step control of reaction uniformity, effectively avoiding the problems caused by uneven reactions in traditional methods.

[0073] (2) Optimization of pre-magnesium reaction by combining solid-solid phase and gas-solid phase: The present invention first performs a solid-phase reaction, that is, the MgO and Mg2Si on the surface of the magnesium matrix and part of the magnesium matrix react with silicon oxide to form a passivation layer to inhibit violent reactions and increase the generation of MgSiO3. This solid-phase reaction stage helps to reduce the intensity of the reaction. Subsequently, the solid-gas phase reaction stage is entered, in which the unreacted magnesium matrix is ​​vaporized and reacts with silicon oxide in a gas-solid phase, further promoting the generation of MgSiO3 and increasing its content. Through this combination, not only the control of the reaction process is optimized, but also the MgSiO3 content of the final product is significantly increased, thereby improving the performance of the pre-magnesium silicon oxide material.

[0074] (3) Improving the specific capacity and material structure of pre-magnesium silicon oxide materials: The introduction of Mg2Si effectively compensates for the loss of specific capacity after pre-magnesium treatment. At the same time, the introduction of MgO increases the content of MgSiO3 generated in subsequent reactions and fills the structural pores generated by porous Si, thereby inhibiting particle aggregation and expansion deterioration, and significantly improving the volume stability and performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0075] Figure 1 This is the XRD spectrum of the pre-magnesium silicon oxide material of Example 1.

[0076] Figure 2 This is the XRD spectrum of the pre-magnesium silicon oxide material of Comparative Example 3. DETAILED DESCRIPTION

[0077] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The reagents and raw materials used in the following examples, such as magnesium powder, are all commercially available.

[0078] In the following examples, the D50 of silicon oxide is 5 μm; the D50 of silicon dioxide is 5 μm, and the purity is >99%; and the purity of magnesium powder is >99%.

[0079] In the following examples, the mixer is from Wuxi Qingxin Powder Equipment Co., Ltd., model VC-10L.

[0080] Example 1

[0081] (1) Preparation of magnesium-based composite materials:

[0082] Weigh 2 kg of magnesium powder and SiO2 powder, of which SiO2 accounts for 2.5% of the total mass. Mix the mixture in a mixer and then transfer it to a vacuum furnace and evacuate it to 10 -5 Pa, raise the temperature to 400°C for heating reaction, keep the temperature constant for 4 hours, cool down and collect the material to obtain a magnesium-based composite material.

[0083] The magnesium-based composite material consists of a magnesium matrix and MgO and Mg2Si distributed on the outer surface of the magnesium matrix; the MgO and Mg2Si are evenly distributed on the outer surface of the magnesium matrix in granular form; the mass ratio of the magnesium matrix to MgO is 29.1:1; and the mass ratio of the magnesium matrix to Mg2Si is 41.5:1.

[0084] (2) Preparation of pre-magnesium silicon oxide materials:

[0085] A total of 5 kg of magnesium-based composite material and silicon oxide powder, of which the magnesium-based composite material accounts for 10% of the total mass, are taken, mixed evenly by a mixer, and then placed in a rotary furnace tube, the rotation is turned on to ensure that the furnace tube rotates at 1 r / min, and 1 L / min of Ar is used for replacement for 2 hours; after the replacement is completed, the heating is turned on, the temperature is increased to 750°C at a rate of 10°C / min, and the temperature is kept at 750°C for 6 hours, and the temperature is lowered, and the material is taken to obtain a mixed material A; the mixed material A is placed in a 3% hydrochloric acid solution for washing, wherein the mixture The volume ratio of material A to hydrochloric acid solution is 0.5:1. After washing, it is placed in water for washing, filtered, dried at 120°C for 3h, and broken up to obtain a mixed material B. 3kg of mixed material B is weighed and placed in a rotary furnace, and the temperature is increased to 800°C at a rate of 5°C / min and kept constant for 90min. At the same time, a mixed gas of argon and acetylene (argon 2L / min, acetylene 2.5L / min) is introduced until the ratio of the mixed gas to the mixed material B is 0.135L / g, and the temperature is lowered to obtain a pre-magnesium silicon oxide material.

[0086] Example 2

[0087] Only the temperature in step (1) was raised to 400° C. for heating reaction, and the other conditions were the same as those in Example 1.

[0088] Example 3

[0089] Only the temperature in step (1) was raised to 600° C. for heating reaction, and the other conditions were the same as those in Example 1.

[0090] Example 4

[0091] Only in step (1), SiO2 accounts for 1% of the total mass, and the other conditions are the same as those in Example 1.

[0092] Example 5

[0093] Only in step (1), SiO2 accounts for 4% of the total mass, and the other conditions are the same as those in Example 1.

[0094] Example 6

[0095] Only in step (2), the magnesium-based composite material accounts for 5% of the total mass, and the other conditions are the same as those in Example 1.

[0096] Example 7

[0097] Only in step (2), the magnesium-based composite material accounts for 15% of the total mass, and the other conditions are the same as those in Example 1.

[0098] Example 8

[0099] Only in step (2), the temperature was raised to 600° C. at a rate of 10° C. / min. The other conditions were the same as those in Example 1.

[0100] Example 9

[0101] Only in step (2), the temperature was raised to 900° C. at a rate of 10° C. / min. The other conditions were the same as those in Example 1.

[0102] Comparative Example 1

[0103] Preparation of pre-magnesium silicon oxide materials:

[0104] A total of 5 kg of magnesium powder and silicon oxide powder were taken, of which magnesium powder accounted for 10% of the total mass. After being mixed evenly by a mixer, the mixture was placed in a rotary furnace tube, and the rotation was turned on to ensure that the furnace tube rotated at 1 r / min. Ar was used for displacement at 1 L / min for 2 h. After the displacement was completed, the heating was turned on, and the temperature was raised to 750 ° C at a rate of 10 ° C / min, and the temperature was kept at 750 ° C for 6 h. The temperature was lowered and the material was taken to obtain a mixed material A. The mixed material A was placed in a 3% hydrochloric acid solution for washing, wherein the mixed material A and the salt were The volume ratio of the acid solution is 0.5:1. After washing, it is placed in water for washing, filtered, dried at 120°C for 3h, and broken up to obtain a mixed material B; 3kg of mixed material B is weighed and placed in a rotary furnace, and the temperature is increased to 800°C at a rate of 5°C / min and kept constant for 90min. At the same time, a mixed gas of argon and acetylene (argon 2L / min, acetylene 2.5L / min) is introduced until the ratio of the mixed gas to the mixed material B is 0.135L / g, and the temperature is lowered to obtain a pre-magnesium silicon oxide material.

[0105] Comparative Example 2

[0106] (1) Preparation of mixed materials:

[0107] Weigh 2 kg of Mg powder and SiO2 powder in total, of which SiO2 accounts for 2.5% of the total mass. Place the mixed material in a mixer and mix it evenly to obtain a mixed material.

[0108] (2) Preparation of pre-magnesium silicon oxide materials:

[0109] Take the above-mentioned mixed material and silicon oxide powder in total 5kg, of which the mixed material accounts for 10% of the total mass, mix them evenly with a mixer, place them in a rotary furnace tube, turn on the rotation to ensure that the furnace tube rotates at 1r / min, use 1L / min Ar displacement, and replace for 2h; after the replacement is completed, turn on the heating, raise the temperature to 750℃ at a rate of 10℃ / min, keep the temperature at 750℃ for 6h, cool down, take the material, and obtain mixed material A; place mixed material A in 3% hydrochloric acid solution for washing, wherein the mixed material The volume ratio of A to hydrochloric acid solution is 0.5:1. After washing, it is placed in water for washing, filtered, dried at 120°C for 3 hours, and broken up to obtain a mixed material B. 3 kg of mixed material B is weighed and placed in a rotary furnace, and the temperature is increased to 800°C at a rate of 5°C / min and kept constant for 90 minutes. At the same time, a mixed gas of argon and acetylene (argon 2L / min, acetylene 2.5L / min) is introduced until the ratio of the mixed gas to the mixed material B is 0.135L / g, and the temperature is lowered to obtain a pre-magnesium silicon oxide material.

[0110] Comparative Example 3

[0111] Weigh 2kg of Mg powder, mix it evenly in a mixer, then transfer it to a vacuum furnace and evacuate it to 10 -5 Pa, raise the temperature to 400℃ for heating and reaction, keep the temperature constant for 4h, cool down and collect the material to obtain a mixed material.

[0112] Take the above-mentioned mixed material and silicon oxide powder in total 5kg, of which the mixed material accounts for 10% of the total mass, mix them evenly with a mixer, place them in a rotary furnace tube, turn on the rotation to ensure that the furnace tube rotates at 1r / min, use 1L / min Ar displacement, and replace for 2h; after the replacement is completed, turn on the heating, raise the temperature to 750℃ at a rate of 10℃ / min, keep the temperature at 750℃ for 6h, cool down, take the material, and obtain mixed material A; place mixed material A in 3% hydrochloric acid solution for washing, wherein the mixed material The volume ratio of A to hydrochloric acid solution is 0.5:1. After washing, it is placed in water for washing, filtered, dried at 120°C for 3 hours, and broken up to obtain a mixed material B. 3 kg of mixed material B is weighed and placed in a rotary furnace, and the temperature is increased to 800°C at a rate of 5°C / min and kept constant for 90 minutes. At the same time, a mixed gas of argon and acetylene (argon 2L / min, acetylene 2.5L / min) is introduced until the ratio of the mixed gas to the mixed material B is 0.135L / g, and the temperature is lowered to obtain a pre-magnesium silicon oxide material.

[0113] Comparative Example 4

[0114] Preparation of pre-magnesium silicon oxide materials:

[0115] Silicon dioxide powder and Mg2Si-4Mg (mass fraction of 97% Mg2Si and 3% Mg, D50=5μm) are placed in a mixer in a mass ratio of 59:41 and mixed evenly. The mixture is then transferred to a tablet press for briquetting. The briquetting product is then placed in an argon-protected tubular furnace and calcined at 650°C. The heating rate is 5°C / min and the insulation time is 3h. After cooling, the product is crushed to D50=1μm to obtain pre-magnesium silicon dioxide material.

[0116] Effect Example

[0117] (1) Element content test

[0118] The pre-magnesium silicon oxide materials of the above embodiments and comparative examples were tested for element content (equipment from Beijing Jitian Instrument Co., Ltd., model ICP-5000), the silicon content and magnesium content in the pre-magnesium silicon oxide materials were tested, the oxygen content in the materials was tested by an oxygen and nitrogen analyzer (equipment from American Leco, model LECO ONH836), and the carbon content in the materials was tested by a carbon and sulfur analyzer (equipment from Sainz Environmental Protection Co., Ltd., model SES-802). The test results are shown in Table 1.

[0119] (2) XRD test

[0120] The XRD spectra of the pre-magnesium silicon oxide materials of Example 1 and Comparative Example 3 are as follows: Figure 1 and Figure 2 As shown. Figure 1 and Figure 2 It can be seen that the pre-magnesium silicic acid material prepared using the magnesium-based composite material of Example 1 has a higher magnesium metasilicate content, which is beneficial to the improvement of the battery cycle life as a pole piece, while the pre-magnesium silicic acid material obtained by reacting the magnesium powder and silicon oxide in Comparative Example 3 has a lower magnesium metasilicate content, which will result in lower battery cycle efficiency as a pole piece.

[0121] (3) Electrochemical performance test

[0122] The pre-magnesium silicic acid materials of the above-mentioned embodiments and comparative examples are prepared into negative electrode sheets: the preparation method of the negative electrode sheet is conventional in the art, comprising the following steps: a mixture of the pre-magnesium silicic acid material, a binder and a conductive agent is slurried and then coated on a copper foil, and then vacuum dried, rolled and slit to obtain a negative electrode sheet.

[0123] The preparation method of lithium-ion battery is conventional in the art, including the following steps: 1 mol / L LiPF6 mixed solvent is used as electrolyte, the mixed solvent is a mixture of ethyl carbonate: dimethyl carbonate: methyl carbonate = 1:1:1 by volume, a polypropylene microporous membrane is used as a diaphragm, and a metal lithium sheet is used as a counter electrode. The above-mentioned electrode made of pre-magnesium silicon oxide is assembled into a button battery in an inert gas glove box system filled with argon. At 25°C, the assembled half-cell is charged and discharged using the LAND battery test system of Wuhan Landian Electronics Co., Ltd. to obtain its capacity, first coulomb efficiency and cycle data. The test results are shown in Table 1.

[0124] Table 1 Test results of Examples 1-9 and Comparative Examples 1-4

[0125]

[0126] By comparing the performance data of Examples 1-9 and Comparative Examples 1-4, it can be seen that the pole pieces made of the pre-magnesium silicon oxide material prepared in Examples 1-9 of the present application have significant advantages in electrochemical performance.

[0127] First, in terms of capacity, the electrodes of Examples 1-9 exhibit higher specific capacity. The capacity of Examples 1-9 ranges from 940 to 1510 mAh / g, and the capacity of most samples exceeds 1200 mAh / g. However, the capacity of Comparative Examples 1-3 is only 1091 to 1114 mAh / g, which is significantly lower than the average level of the Examples. In particular, Example 6 has a capacity as high as 1510 mAh / g.

[0128] Secondly, in terms of the first coulomb efficiency, the pole pieces prepared in Examples 1-9 also have obvious advantages. The first coulomb efficiency of Examples 1-9 ranges from 90.1% to 95.3%, which is significantly higher than the first efficiency range of 81.7% to 84.5% of Comparative Examples 1-3. For example, the first efficiency of Example 7 reaches 95.3%, which is 10.8% higher than the highest value of 84.5% in Comparative Example 1, indicating that the materials of the Examples have higher efficiency during the first charge and discharge process.

[0129] In addition, in terms of cycle performance, the pole pieces prepared in Examples 1-9 show a better capacity retention rate. The 100-cycle cycle capacity retention rate of Examples 1-9 is between 79.4% and 93.7%, while the retention rate of Comparative Examples 1-3 is only 68.6% to 71.7%. Too much magnesium silicide is added in Comparative Example 4, causing part of the silicon to aggregate. Although only 3% is added, the agglomeration of this part of silicon will lead to a significant decrease in the performance of the entire battery cell, and its 100-cycle cycle capacity retention rate is only 63.3%. Among them, the cycle capacity retention rate of Example 7 reaches 93.7%, which is significantly higher than 71.7% of Comparative Example 1, showing the stability advantage of this material in long-cycle use.

Claims

1. A magnesium-based composite material, characterized in that: The magnesium-based composite material comprises a magnesium matrix and MgO and Mg2Si distributed on the outer surface of the magnesium matrix; The MgO and the Mg2Si are evenly distributed on the outer surface of the magnesium matrix in a granular form; The mass ratio of the magnesium matrix to the MgO is greater than 1.71:1; The mass ratio of the magnesium matrix to the Mg2Si is greater than 2.45:

1.

2. The magnesium-based composite material according to claim 1, characterized in that: The mass ratio of the magnesium matrix to the MgO is 29.1:1; And / or, the mass ratio of the magnesium matrix to the Mg2Si is 41.5:

1.

3. A method for preparing a magnesium-based composite material, characterized in that: It includes the following steps: Mix magnesium powder and SiO2 powder evenly and heat to react; The mass ratio of the magnesium powder to the SiO2 powder is greater than 2.3:1; The temperature of the heating reaction is ≤900°C.

4. The method for preparing the magnesium-based composite material according to claim 3, characterized in that: The preparation method of the magnesium-based composite material meets one or more of the following conditions: (1) The mass ratio of the magnesium powder to the SiO2 powder is (20-100):1, preferably (24-99):1, for example 39:1; (2) The temperature of the heating reaction is 200°C-900°C, preferably 400°C-600°C; (3) The uniform mixing operation is carried out in a mixer; (4) The heating reaction is carried out in a vacuum furnace; (5) The heating reaction time is 2h-6h, for example 4h; (6) The vacuum degree of the heating reaction is ≤10 -5 Pa.

5. A magnesium-based composite material, characterized in that: The magnesium-based composite material is made by the preparation method of the magnesium-based composite material according to claim 3 or 4.

6. A pre-magnesium silicon oxide material, characterized in that: The pre-magnesium silicon oxide material comprises a core and a carbon coating layer coated outside the core, wherein the core comprises the magnesium-based composite material according to any one of claims 1 to 2 or 5, a magnesium silicate compound and silicon oxide; the carbon coating layer is an amorphous carbon layer; The magnesium-based composite material and the magnesium silicate compound are deposited in the pores and on the surface of the silicon oxide; The magnesium silicate compounds are MgSiO3 and Mg2SiO4; The weight percentage of silicon element in the pre-magnesium silicon oxide material is 49 wt%-54 wt%, for example 49.6 wt%; and / or, the weight percentage of magnesium element in the pre-magnesium silicon oxide material is 2.5 wt%-12.5 wt%, for example, 7.5 wt%; and / or, the weight percentage of oxygen element in the pre-MgO-SiO material is 34 wt%-41.5 wt%, for example, 39.8 wt%; and / or, the weight percentage of carbon element in the pre-magnesium silicon oxide material is 2.5 wt%-4 wt%, for example, 3.1 wt%; Wherein, wt% is the percentage of the weight of each element to the total weight of the pre-magnesium silicon oxide material.

7. A method for preparing a pre-magnesium silicon oxide material, characterized in that: The magnesium-based composite material according to any one of claims 1 to 2 or 5 is mixed evenly with silicon oxide, and calcined to obtain a mixed material A; Then, the mixed material A is pickled in an acidic solution to obtain a mixed material B; The mixed material B is then carbon coated in a mixed gas containing a carbon source gas and an inert gas.

8. The method for preparing the pre-magnesium silicon oxide material according to claim 7, characterized in that: The preparation method of the pre-magnesium silicon oxide material meets one or more of the following conditions: (1) The mass ratio of the silicon oxide to the magnesium-based composite material is greater than 2.3:1, for example, 9:1; (2) The uniform mixing operation is carried out in a mixer; (3) After the mixing is uniform, the step of replacing with an inert gas is also included before the calcination; Preferably, the inert gas is a combination of one or more of argon, helium or nitrogen, such as argon; Preferably, the inert gas replacement is performed in a rotary kiln, wherein the rotation speed of the rotary kiln is more preferably 0.5 r / min-2 r / min, for example 1 r / min; Preferably, the flow rate of the inert gas is 0.5 L / min-2 L / min, for example, 1 L / min; Preferably, the inert gas replacement time is 1h-4h, for example 2h; (4) The calcination reaction temperature is ≤ 900°C, preferably 600-900°C, for example 750°C; (5) The calcination reaction time is 4h-8h, for example 6h; (6) The heating rate from room temperature to the calcination reaction temperature is 5°C / min-15°C / min, for example, 10°C / min; (7) The acidic solution is a combination of one or more of hydrochloric acid, acetic acid or sulfuric acid; Preferably, the concentration of the acidic solution is 3%-8%, for example 3%-6%, where % is the mass percentage concentration; Preferably, the volume ratio of the mixed material A to the acidic solution is less than or equal to 2:1, preferably (0.5-2):1; (8) The pickling process also includes a water washing process; (9) The pickling process also includes a drying process; Preferably, the drying temperature is ≤200°C, preferably 120°C-200°C, and the drying time is ≤48h, preferably 3h-48h; (10) The carbon source gas is acetylene; (11) The inert gas is a combination of one or more of argon, helium or nitrogen, such as argon; (12) The flow rate ratio of the inert gas to the carbon source gas is 1:(1-1.5); Preferably, the flow rate of the inert gas is 2 L / min, and the flow rate of the carbon source gas is 2.5 L / min; (13) The carbon coating reaction temperature is 600°C-1000°C, for example 800°C; (14) The heating rate from room temperature to the reaction temperature of carbon coating is 1°C / min-10°C / min, for example, 5°C / min; (15) The reaction time of the carbon coating is 0.5 h -2 h, for example 1 h; (16) The ratio of the mixed gas to the mixed material B is 0.010 L / g to 0.200 L / g, where L / g refers to the volume of the mixed gas required per gram of the mixed material B; Preferably, the dosage ratio of the mixed gas to the mixed material B is 0.135 L / g.

9. A pre-magnesium silicon oxide material, characterized in that: The pre-magnesium silicon oxide material is prepared by the preparation method described in claim 7 or 8.

10. Use of the pre-magnesium silicon oxide material according to claim 6 or 9 in preparing a pole piece; Preferably, the electrode is a negative electrode; Preferably, the preparation method of the pole piece is to mix the pre-magnesium silicon oxide material, the binder and the conductive agent, apply the mixture on the copper foil, vacuum dry, roll and cut.

11. A lithium ion battery, characterized in that: It comprises the pre-magnesium silicon oxide material as claimed in claim 6 or 9.

Citation Information

Patent Citations

  • Method for preparing silicon-based anode material of lithium-ion battery

    CN101533907A

  • Method for preparing silicon monoxide powder by low-temperature solid-phase method

    CN116873937A

  • High-capacity high-first-effect silicon monoxide-based composite negative electrode material, preparation method and application

    CN117352715A

  • Pre-magnesium silicon oxide material, preparation method and application thereof and lithium ion battery

    CN117613223A

  • Magnesium base composite material and method for production thereof

    CN1633512A